KAFE TENDA DAN SEKSUALITAS TERSELUBUNG - Syahril Ramadhan; Syamsumarlin Syamsumarlin; Akhmad Marhadi (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This study aims to find out and to describe the prostitution transactions and the relationship between cafe owners, pimps and commercial sex workers at tent cafes in Kendari Beach, Kendari City. Data collection is done by direct observation techniques and in-depth interviews. The data is analyzed by descriptive qualitative. The results show that the prostitution transactions in tent cafes in Kendari Beach. It is caused by the lack of modal and low income in selling culinary. One way to get a higher modal is to make their cafe as a place for prostitution transactions. Prostitution transactions involve cafe owners, pimps and prostitutes. Keywords: tent cafes, prostitutions, lifestiles